(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the peculiarities of functioning of the conjunctions in the structure of complex sentences with inferior conditional part on material of Ukrainian. The modification of categorical semantics of hypothetic depending upon the choice of conjunctions, which are manifestations of unreal semantic and syntactic relations, has been investigated.